2014
DOI: 10.1063/1.4881941
|View full text |Cite
|
Sign up to set email alerts
|

Flow control of an oblique shock wave reflection with micro-ramp vortex generators: Effects of location and size

Abstract: The effects of micro-ramp height and location on a shock induced separation bubble were quantified using planar particle image velocimetry measurements. Conditional averaging was used to show that the amount of separation is related to the momentum flux in the near-wall region (< 0.5δ) of the incoming boundary layer. The momentum flux added to this region scales linearly with micro-ramp height and larger microramps are shown to be more effective in stabilizing the interaction. Full boundary layer mixing is att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 23 publications
4
61
0
1
Order By: Relevance
“…The resulting half sweep angle (α) and incidence angle (β) are both 24 • . The geometry of the micro-ramp follows the optimization study by Anderson et al (2006) and is one of the most reported in the literature (Babinsky et al 2009;Herges et al 2010;Sun et al 2012;Giepman, Schrijer & van Oudheusden 2014). Its schematic layout is illustrated in figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting half sweep angle (α) and incidence angle (β) are both 24 • . The geometry of the micro-ramp follows the optimization study by Anderson et al (2006) and is one of the most reported in the literature (Babinsky et al 2009;Herges et al 2010;Sun et al 2012;Giepman, Schrijer & van Oudheusden 2014). Its schematic layout is illustrated in figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The micro-ramp geometry has been widely used as a flow control device to enhance boundary layer mixing, promote transition and avoid unwanted separation (Berry et al 2001;Lin 2002). In the special case of shock wave boundary layer interactions (SWBLI) with an incoming supersonic turbulent boundary layer, the micro-ramp has also gained substantial research attention due to its effectiveness in reducing separation (Dolling 2001;Babinsky, Li & PittFord 2009;Giepman, Schrijer & van Oudheusden 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The incompressible shape factor H i (see Eq.1) is a measure of the fullness of the boundary layer and is often used to assess the 'health' of the boundary layer and its resilience to separation. 25 The added momentum flux E (see Eq.2) is a metric that was introduced in the work of Giepman et al 9 and provides a measure of the momentum flux that has been added to the near-wall region (<0.43δ 99 ) of the flow by the action of the micro-ramp. It was found that the added momentum flux scales linearly with the micro-ramp height h and that x scales with the boundary layer thickness δ 99 instead of the micro-ramp height h. The added momentum flux was found to increase upto x ∼ 5.7δ 99 , after which a plateau is reached and virtually no extra momentum is added or removed.…”
Section: B Piv Resultsmentioning
confidence: 99%
“…However, besides transporting highmomentum fluid towards the wall, micro-ramps also incur a drag penalty in the form of a low-momentum wake, which steadily lifts off from the surface when moving downstream. The location and strength of the wake were also found 5,[8][9][10][11] to scale proportionally with micro-ramp height.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation